2017
DOI: 10.1111/tpj.13622
|View full text |Cite
|
Sign up to set email alerts
|

The redox‐sensitive module of cyclophilin 20‐3, 2‐cysteine peroxiredoxin and cysteine synthase integrates sulfur metabolism and oxylipin signaling in the high light acclimation response

Abstract: The integration of redox- and reactive oxygen species-dependent signaling and metabolic activities is fundamental to plant acclimation to biotic and abiotic stresses. Previous data suggest the existence of a dynamically interacting module in the chloroplast stroma consisting of cyclophilin 20-3 (Cyp20-3), O-acetylserine(thiol)lyase B (OASTL-B), 2-cysteine peroxiredoxins A/B (2-CysPrx) and serine acetyltransferase 2;1 (SERAT2;1). The functionality of this COPS module is influenced by redox stimuli and oxophytod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 65 publications
(90 reference statements)
1
22
0
Order By: Relevance
“…Since antioxidant defense involves the accumulation of two important thiol-containing compounds, cysteine and glutathione [46,47], we can expect sulfur metabolism to change under salt stress imposition. In this context, it is interesting to note that recent studies suggested the existence of a dynamically interacting module in the chloroplast stroma consisting of a peptidylprolyl isomerase (cyclophilin), two 2-cysteine peroxiredoxins A/B and a cysteine synthase, that integrate sulfur metabolism and oxylipin signaling during the acclimation to high light stress [48]. In salt-stressed KNO 3…”
Section: Discussionmentioning
confidence: 99%
“…Since antioxidant defense involves the accumulation of two important thiol-containing compounds, cysteine and glutathione [46,47], we can expect sulfur metabolism to change under salt stress imposition. In this context, it is interesting to note that recent studies suggested the existence of a dynamically interacting module in the chloroplast stroma consisting of a peptidylprolyl isomerase (cyclophilin), two 2-cysteine peroxiredoxins A/B and a cysteine synthase, that integrate sulfur metabolism and oxylipin signaling during the acclimation to high light stress [48]. In salt-stressed KNO 3…”
Section: Discussionmentioning
confidence: 99%
“…Recently, overexpression of non‐specific LTPs was shown to increase glutathione contents and resistance to mycotoxins (McLaughlin et al ). LTP3 and LTP4 transcript levels also respond strongly in H‐light exposed A. thaliana mutants devoid of the chloroplast thiol peroxidases 2‐cys peroxiredoxins A/B (Müller et al ). Similar to the first set of experiments, transcripts were very strongly upregulated in pad 2 exposed to H‐light ( HSP17.4 , HSP17.6a , HSP20‐like2 and LTP3 ) and slightly for HSP20‐like1 , while the ascorbate deficiency increased LTP3/4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…In pathogen-infected plants, RES have been reported to stimulate the expression of defensive genes and to directly modify proteins [71]. For example, OPDA has been reported to bind cyclophilin 20-3 (CYP20-3), a binding protein that regulates stress-responsive cellular redox homeostasis [72,73]. Regardless of the defence route, it is well known that the excessive production of electrophilic molecules can disrupt natural cellular functions and, eventually, cause cell collapse [74].…”
Section: The Road To the Next Levelmentioning
confidence: 99%